An exploratory study on factors contributing to aggressive behavior among adolescents in selected schools, Sri Amritsar, Punjab - Kaur Bajwa*, Ramandeep; Kaur, Gurjeet; Kaur, Sukhbir (International Journal of Nursing Research, 2023)
Introduction: Adolescence is the period of physical and psychological development from the onset of puberty to maturity. It is also referred to as teenage years or youth. Among deviant human behaviors in the society, aggression appears to be the most prevalent and perturbing. Aim- The aim of the study was to explore the factors contributing to aggressive behavior among adolescents of selected schools of district Amritsar. Method: Enrolling 200 adolescents studying at selected schools of district Amritsar, Punjab, conducted an exploratory study. The adolescent’s enrollment was done by simple random sampling technique. The Aggression Scale by G.P Mathur and Rajkumari Bhatnager was used to assess the level of aggression score of adolescents. Selfstructured questionnaire was used to assess the factors contributing to aggressive behavior. Result: The study revealed that majority of the adolescents were having average (89%) level of aggression and there was significant association between family (occupation of father and order in the family) and personal factors (substance abuse) with level of aggression